Structuring the Mentoring Relationship: Expectations and Boundaries - Nameeta Dookeran; Robert Fuhlbrigge; Barbara Gottlieb; Francine Grodstein; Audrey Haas; Carol Nadelson; Ellen Seely; Frederick Schoen; Lawrence Tsen; Jonathan Borus (Association of American Medical Colleges, 2015)
Abstract Introduction The Faculty Mentoring and Leadership Program is an innovative, faculty development program that has been implemented annually since it was first designed in 2008. The program consists of a series of nine sessions that were designed primarily as a peer-learning experience for mid-career and senior faculty physicians, and scientists who serve as mentors. This session can be stand-alone or used in conjunction with other topical sessions that were developed as part of the Faculty Mentoring Leadership Program, a nine-session, peer learning experience for a cohort of mid-career and senior faculty physician and scientist mentors to enhance their mentoring effectiveness. The cases and topics are relevant and adaptable for mentors across the academic continuum. The learning environment is enhanced by the interactive, case-based nature of the sessions with a cohort of faculty from various disciplines. Methods This 90-minute session usually creates energetic discussion in both small and large groups about how to optimally structure the mentoring relationship. A week before this session, preassigned readings are distributed, and participants are asked to give input via e-mail regarding their experiences and challenges in structuring the mentoring relationship. The session itself consists of facilitated small breakout group discussions of a case with associated case questions. Following this, small groups report back to the large group, with further facilitated discussions focusing on the themes raised by the case and on mentoring agreements. Learning pearls are intentionally distributed at the end of the session to summarize and reinforce key take-home points, many of which the participants themselves will have raised in the preceding discussion. Results On a 1-5 scale (1 = poor, 5 = excellent) over the five cohorts of the Faculty Mentoring Leadership Program (2009-2014), this session has averaged a 4.59 rating at the end of the 90-minute session and a 4.63 rating in the retrospective evaluation of the entire nine-month course after its end. Discussion The increased rating at the end of the course may suggest that over the nine sessions participants became even more aware of the value of clearly structuring the mentoring relationship as well as the perils inherent in unclear structure and expectations.